English varieties in the Year-7 coursebook taught in Indonesia - Yuni Hardianti; Sudarsono Sudarsono (Journal of English Language Teaching Innovations and Materials (Jeltim), 2021)
The present research was designed to investigate the English varieties encountered in an English coursebook applied throughout Indonesia. It applied a descriptive analysis. The data were sorted out from corpora. The research found out that the coursebook applied in Indonesian schools included different varieties of English. They were American, British, and American and British-like. The varieties here covered vocabulary, spelling, and grammar.